Successful live birth after rescue ICSI following failed fertilization - Neeta Singh; Neena Malhotra; Unnati Shende; Abanish Tiwari (Wolters Kluwer Medknow Publications, 2013)
In a conventional IVF cycle unexpected complete fertilization failure may occur in 10-25% of infertile women. To overcome this barrier of fertilization failure, some investigators have suggested intracytoplasmic sperm injection (ICSI) on day 1 of an unfertilized mature oocyte, the so called "rescue ICSI". We report a case of fertilization failure followed by rescue ICSI resulting in a live birth. Although the success of rescue ICSI is still questionable, this procedure is worth an attempt in order to give the best chance to the couple in that cycle.